2009
DOI: 10.1186/1476-4598-8-68
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-induced prostate cancer cell death involves concomitant activation of caspase and lysosomal pathways and is attenuated by LEDGF/p75

Abstract: Background: Hormone-refractory prostate cancer (HRPC) is characterized by poor response to chemotherapy and high mortality, particularly among African American men when compared to other racial/ethnic groups. It is generally accepted that docetaxel, the standard of care for chemotherapy of HRPC, primarily exerts tumor cell death by inducing mitotic catastrophe and caspase-dependent apoptosis following inhibition of microtubule depolymerization. However, there is a gap in our knowledge of mechanistic events und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 49 publications
6
101
0
Order By: Relevance
“…In a previous study we reported that LEDGF/p75 overexpression in PCa cells promoted resistance against caspase-independent cell death induced through lysosomal membrane permeabilization (LMP) by the taxane drug docetaxel (DTX), the gold standard for advanced PCa chemotherapy [18]. These results were consistent with studies in other cancer cell types demonstrating that LEDGF/p75 overexpression promoted cellular protection against LMP-inducing drugs [19].…”
Section: Introductionsupporting
confidence: 75%
“…In a previous study we reported that LEDGF/p75 overexpression in PCa cells promoted resistance against caspase-independent cell death induced through lysosomal membrane permeabilization (LMP) by the taxane drug docetaxel (DTX), the gold standard for advanced PCa chemotherapy [18]. These results were consistent with studies in other cancer cell types demonstrating that LEDGF/p75 overexpression promoted cellular protection against LMP-inducing drugs [19].…”
Section: Introductionsupporting
confidence: 75%
“…Unusually, high expression of LEDGF promotes cell survival, and may initiate cellular abnormalities or promote tumor formation. 6,65,66 Low expression leads to negative regulation of survival signaling. Recent studies have investigated various features of LEDGF protein, regulation of its gene and its role in cancer and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…6A). In prostate cancer cells, docetaxel-induced cell death involves the processing of caspases, particularly the executioner caspase-3, an event associated with the activation of PARP, a canonical caspase-3 substrate (29). In scrambled RNAi-transfected PC-3, a diminution of both 32 kDa unprocessed caspase-3 and 116 kDa unprocessed PARP expression during treatment with docetaxel was found (Fig.…”
Section: Chemotherapy-induced Cell Death Is Inhibited By Spl Knockdowmentioning
confidence: 94%